Kinetin applications alleviate salt stress and improve the antioxidant composition of leaf extracts in Salvia officinalis - Tounekti, Taïeb (Plant physiology and biochemistry : PPB, 2011)
Copyright © 2011 Elsevier Masson SAS. All rights reserved.